Myofibroblasts have an impact on expression, dimerization and signaling of different ErbB receptors in OSCC cells. (2nd January 2017) - Büttner, Robert; Berndt, Alexander; Valkova, Christina; Richter, Petra; Korn, Alexander; Kosan, Christian; Liebmann, Claus
Abstract: Introduction : Receptors of the ErbB family belong to the key players in cancer development and are targets of several therapeutic approaches. Their functional dependency on the tumor microenvironment, especially on CAFs is albeit still poorly understood. Our objective was to investigate the impact of CAF secretome on ErbB receptor expression and signaling behavior in OSCC. Methods : Stimulation of PE/CA-PJ15 OSCC cells with conditioned media of TGF-β1-activated fibroblasts was used as model system for CAF to cancer cell communication. Thereby costimulation with inhibitors against matrix metalloproteinases (MMPs), epidermal growth factor receptor (EGFR), MAPK/ERK kinase (MEK), phosphoinositide-3 kinase (PI3-K), signal transducer and activator of transcription 3 (Stat3) or knockdown of Her3 by siRNA was utilized for detailed investigation of the expression, dimerization and signaling pattern of ErbB in western blot and coimmunoprecipitation. Results : Our results show that soluble factors in activated fibroblast secretome stimulate metalloproteinase activity in the membrane of cancer cells. Thereby ligands are released that activate EGFR and subsequently upregulates EGFR expression via the STAT3 pathway. Simultaneously, the expression of PKCɛ was enhanced via a PI3-kinase/Akt-mediated pathway and a negative feedback regulation loop on EGFR downstream signaling generated. Furthermore, the activated fibroblasts secretome stimulated the highly oncogenic hetero-dimerization between HER3 and p95HER2. That protein association is inversely dependent on the expression level of HER3. Conclusions : Our results demonstrate that the activated fibroblasts secretome can induce a counterbalanced regulation of protein expression, downstream signaling and the dimerization patterns of different ErbB receptor subtypes in the cancer cell. Thus, the combinatorial targeting of CAFs and selective ErbB receptor subtype inhibitors may provide a useful approach in cancer therapy.